Pengembangan Web Educaplay Berbasis Cooperative Script pada Materi Keragaman Budaya untuk Siswa Kelas 3 - Muhammad Afif Musthofa; Erwin Putera Permana; Efa Wahyu Prastyaningtyas (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Cultural Diversity learning in elementary schools requires interactive media to enhance student engagement and learning outcomes. However, the use of less engaging learning media remains a challenge in the learning process. This study aimed to develop a Cooperative Script-based Educaplay Web learning media and determine its validity, practicality, and effectiveness in improving the learning outcomes of third-grade students at SDN 2 Puyung. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 26 third-grade students. The results showed that the developed media achieved a validity score of 89%, categorized as valid, and a practicality score of 91.5%, categorized as very practical. The media was also effective in improving student learning outcomes, as indicated by an increase in the average score from 66.7 on the pretest to 83.4 on the posttest, with a learning mastery rate of 90%. The learning gain score of 0.50 was classified as moderate. These findings indicate that the Cooperative Script-based Educaplay Web learning media is a feasible, effective, interactive, and practical alternative for teaching Cultural Diversity in elementary schools